Moderating Role of Foreign Investor Characteristics on the relationship between Regulatory Factors of International Trade and Environmental Degradation in UAE - Albahar, Saood Mohammad Hassan; Islam, Rabiul (South Asian Journal of Social Sciences and Humanities, 2022)
The study has been conducted to analyze the moderating role of economic factors of foreign investor over the relationship between regulatory factors and environmental degradation in Dubai. The study has been conducted in Dubai considering the country as a fastest growing economy and attracting foreign direct investment in all fields. For the purpose of fulfilment of the study objectives the research developed two hypotheses. The hypothesis was tested over a sample of 335 responses generated from the executives of multinational firms of Dubai. The results confirmed that regulatory factors have a direct impact over environmental degradation, similarly, foreign investor characteristics also have a significant moderating role over the significant relationship between regulatory factors of foreign direct investment and environmental degradation. The study is important for the policy makers to develop such rules that negative influence over the environment may be curtailed.